Using the method of circuit training in the development of high-speed and power abilities of 15-16-year-old basketball players - Irina Pomeshchikova; Natalііa Chucha; Iryna Shyriaeva (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to determine the effectiveness of using a set of high-speed and power exercises by the circular training method in the training process of 15-16-year-old basketball players. Material and methods: two groups of 15-16-year-old basketball players of Kharkov BC "Junior" in the total number of 20 sportsmen (control group, n=10, experimental group, n=10) took part in the research. The pedagogical experiment lasted 2 months and consisted of the introduction in the educational and training process of the experimental group of specially selected exercises which were used by means of the method of circuit training. The set of exercises included jumps through a gymnastic bench, jumps out from a deep squat, jumps in-depth, throwing of a stuffed ball sitting and standing, jumps up with reaching out the suspended ball. The offered set of exercises was applied on each training classes at the beginning of the main part. The total number of training classes in a week of control and experimental group equaled four lasting 135 minutes. Results: introduction to the educational and training process of experimental group of 15-16-year-old basketball players of specially selected exercises aimed at the development of high-speed and power abilities with using the method of circuit training, was revealed the reliable improvement of indicators of test exercises: standing long jump (t=2,13; р<0,05), standing high jump (t=2,14; р<0,05), high jump from running start (t=2,24; р<0,05). The reliable difference wasn't revealed in the test "Throwing of a stuffed ball weighing 1 kg, standing" (t=0,86; р>0,05). Conclusions: the improvement of manifestation of indicators of high-speed and power abilities of 15-16-year-old basketball players of the experimental group after the introduction of specially selected exercises with using the method of circuit training was: in the test "Standing long jump" - 2,73%, "Standing high jump" - 5,54%, "High jump from running start" - 6,32%, "Throwing of a stuffed ball weighing 1 kg, standing" - 7,62%.